1991
DOI: 10.1128/iai.59.9.3191-3198.1991
|View full text |Cite
|
Sign up to set email alerts
|

The e (P4) outer membrane protein of Haemophilus influenzae: biologic activity of anti-e serum and cloning and sequencing of the structural gene

Abstract: Outer membrane proteins of nontypeable (NT) Haemophilus influenzae are among the major candidates for inclusion in vaccines against these organisms. This article reports the purification of the e (P4) lipoprotein of H. influenzae and the subsequent production of antiserum directed against this protein. The anti-e polyclonal serum cross-reacted with e protein in multiple clinical NT H. influenzae isolates. Monoclonal antibody analysis of e protein showed at least one surface-exposed epitope to be conserved amon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
55
0

Year Published

1996
1996
2010
2010

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(56 citation statements)
references
References 35 publications
(39 reference statements)
1
55
0
Order By: Relevance
“…The following specific primers were used for the amplification of the hel gene DNA fragment: AR15 (26' mer): 5'-ATTGGATCCGAAT-TCTTAAAAGGAAT-3'; and AR16 (30' mer): 5'-ATTAA-ATATTGGATCCAGTAAAAACTGAGC-3'. These oligonucleotides were designed to anneal to the flanking DNA sequences of the hel gene at bp position 1-18 for AR15, and 1032-1047 for AR16, according to the DNA sequence published by Green et al (17). BamHI restriction sites were designed into the 5' ends of primers AR15 and AR16.…”
Section: Methodsmentioning
confidence: 99%
“…The following specific primers were used for the amplification of the hel gene DNA fragment: AR15 (26' mer): 5'-ATTGGATCCGAAT-TCTTAAAAGGAAT-3'; and AR16 (30' mer): 5'-ATTAA-ATATTGGATCCAGTAAAAACTGAGC-3'. These oligonucleotides were designed to anneal to the flanking DNA sequences of the hel gene at bp position 1-18 for AR15, and 1032-1047 for AR16, according to the DNA sequence published by Green et al (17). BamHI restriction sites were designed into the 5' ends of primers AR15 and AR16.…”
Section: Methodsmentioning
confidence: 99%
“…We postulated that if the lower abundance of lic1 mRNA in aerobic cells accounts for the aerobic decrease in PC epitope levels, then generating elevated amounts of lic1 mRNA aerobically will cause elevated aerobic PC epitope levels. We engineered a strain Rhel-licA, in which the native licA gene is under the transcriptional control of a strong promoter from the hel gene (The Institute for Genomic Research, TIGR locus HI0693) encoding an outer-membrane lipoprotein involved in NAD and NMN uptake (Green et al, 1991;Reilly et al, 1999;Kemmer et al, 2001), which we had found by Northern analysis to be highly expressed (data not shown). Rhel-licA contains the hel promoter immediately 5¢ of three in-frame potential licA initiation codons and an in-frame deletion of the CAAT repeat units (Experimental procedures).…”
Section: Effects Of Lica Mrna Overexpression On Pc Epitope Levelsmentioning
confidence: 99%
“…NosL has a presequence of 24 amino acids that features the cleavage site, -3 LTGTCGE -1-3, of a lipoprotein [45]. The signal sequence shows similarity to that of an outer membrane lipoprotein from Huernophilus influenzae [46]. Acylation of the terminal cysteine residue might anchor NosL in the outer membrane.…”
Section: E a A S M Q H G G M H D H A P N Gmentioning
confidence: 99%